Evaluation of procalcitonin as a predictor of severity of acute appendicitis - Dharwal, Vikrant; Bharti, Ramesh; Verma, Amar; Chaudhary, Rajesh; Dogra, Ravi Singh; Kumar, Raj (International Surgery Journal, 2020)
Background: Acute appendicitis is the most common surgical emergency worldwide. The treatment of choice is emergency appendectomy. A delayed diagnosis and hence a delayed treatment increases the complication rate. Despite the best efforts negative appendectomy rate is still high since there is no single best test available to reach the diagnosis. Methods: This was an institutional study conducted at DRPGMC Tanda, comprising of 28 patients and 7 healthy controls. The patients with clinical diagnosis of acute appendicitis were subjected to appendectomy after taking a blood sample for serum procalcitonin and performing an ultrasonogram of abdomen. Results: We observed that mean levels of procalcitonin (PCT) were significantly higher in patients of acute appendicitis in comparison to healthy controls. The range of PCT levels in group 2 i.e., patients with uncomplicated acute appendicitis were from 0.54 to 0.74 ng/ml with mean value of 0.61 ng/ml, whereas in group 3 i.e. patients with complicated acute appendicitis, the range were from 1.14 to 2.56 ng/ml with mean value of 1.62 ng/ml. PCT levels were significantly higher in group 3 as compared to group 1 and group 2 (p<0.0001). In group 2, mean PCT levels were significantly higher in comparison to group 1 (p<0.0001). Statistical analysis of our data shows a cut-off value of procalcitonin to be 0.203 ng/ml. We observed sensitivity and specificity of PCT to be 96% and 100% respectively. Conclusions: This study concludes that levels of serum PCT can be used as a laboratory marker for making a diagnosis of acute appendicitis and also for predicting its severity.